Proximity and price co-movement in West African rice markets - Caroline Mengel; Stephan von Cramon-Taubadel (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
This study explores the link between proximity and price cointegration between two markets, where proximity is captured with variables for geographical, political and cultural distance. Linear and threshold cointegration is tested for a set of 756 rice market pairs in 6 West African countries, with threshold specifications accounting for transaction costs. Whether proximity influences price transmission is determined in a second step with a multinomial logistic regression. The estimation produces robust and statistically significant evidence of a link with air-line and road distance, international borders, contiguity and a common language. We conclude that proximity matters for market integration processes in West African rice markets.
Keywords: C32; D23; L11; Q11; Q17; 330; West Africa; cointegration; developing countries; agricultural trade; rice; commodity prices; transaction costs; regional integration